Living with fragility : children in New Crossroads - Henderson, Patricia Catherine (Social Anthropology, 2015)
Living with Fragility, traces the lives of sixteen African children between 1992 and 1995. It explores the intimate spaces of children's social relationships and charts discontinuities they experienced. The eight girls and eight boys, aged between and sixteen years, resided in New Crossroads, Cape Town, a suburb marked by poverty, inadequate schooling, and a history of violent intervention by the apartheid state and other power holders. The thesis shows that institutions of childhood are fragile, that children's social relationships are fragmented, as are their senses of self. Fragility is traced within and the social domains the children inhabited and created. The thesis argues that children's senses of self are subject to flux and interruption. Narrative ethnographies about the children demonstrate their individuality. Nuanced descriptions of children and the changes in their lives over time challenge bald categorisations of, for example, the African child, or, youth at risk. The descriptions demonstrate the agency, dexterity and responsibilities of children in fluid circumstances and lead to a critical appraisal of predominant notions of childhood. The work also outlines processes of social and relational reconstitution to which children and care-givers had recourse. Methods used in gathering data included a series of formal interviews conducted in Xhosa (the children's first language) in which economic descriptions of households, life histories, social networks, and ritual and religious affiliations of children and care-givers were sought. The formal interviews complemented by repeated visits to each child's home to record changes time. The sixteen children were brought together in workshops where discussion directed towards themes to do with mobility between care-givers, violence, sexuality and senses of self the data were enriched by use of dramatic improvisations and drawings. Improvisations yielded insight into children's bodily style and their critical appraisal of trends in social relationships in New Crossroads. The ethnography describes the social circumstances of children in urban South Africa. It is analysed through use of an eclectic set of theoretical fragments because they resonate with the study's ethnographic material. The eclecticism impelled by the data raises questions.